Institutions: Everywhere But Not Everything. (July 2020) - Ocasio, William; Gai, Shelby L.
Recent critiques by Alvesson, Hallett, and Spicer have characterized neo-institutional theory (NIT) specifically as confronting a mid-life crisis and institutional theory (IT) more generally as uninhibited. While offering valid points, these critiques lack a fundamental understanding of how organizational institutionalism (OI) has become distinct from NIT. In contrast to NIT's master hypothesis of isomorphism and focus on structural determinism, OI has made remarkable progress in explaining institutional variation and change. Notably, like organization theory more generally, OI is not a coherent theory, but rather a big tent community with its own set of internal differences, and at times confusing concepts. Rather than abandoning the concept of institutions, we suggest continued progress in OI requires greater clarification. Institutions are everywhere, but not everything, so it is important for researchers to specify which institutions are being studied, distinguish between institutions and culture, and ascertain the relationship between institutions and organizations.